miR-203 inhibits tumor cell migration and invasion via caveolin-1 in pancreatic cancer cells - MIAO, LIFENG (D.A. Spandidos, 2014)
Pancreatic cancer is one of the most lethal malignant diseases with the poorest prognosis and is the fourth leading cause of tumor-associated mortality in the industrialized world. microRNAs (miRNAs or miRs) are small noncoding RNAs of approximately 22 nucleotides long that are able to function as oncogenes or tumor suppressors in human cancer. In our study, overexpression of miR-203 in Panc-1 cells is sufficient to reduce migratory ability and invasiveness, and to induce upregulation of epithelial markers (Snail, ZO-1 and β-catenin) followed by a decrease of mesenchymal marker expression (Zeb-1, vimentin and fibronectin). We also found that the caveolin-1 mRNA or protein levels are modulated by miR-203 in Panc-1 cells. We found that exogenous miR-203 altered the level of cell migration and invasion, and the expression of associated proteins following caveolin-1 knockdown by small interfering RNA. These results demonstrate that miR-203 inhibits cell migration and invasion via caveolin-1 in pancreatic cancer cells, suggest that miR-203 expression may be a useful indicator of the metastatic potential and provide a new therapeutic target in this common malignancy.